2016
DOI: 10.4269/ajtmh.16-0385
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficacy of Molecular Techniques for Detection and Identification of Leishmania Species in Human Whole Blood and Skin Samples from Ecuador

Abstract: Abstract. Microscopic examination is the standard method for diagnosis of cutaneous and mucocutaneous leishmaniasis despite its low sensitivity. This study compared the diagnosis efficacy of microscopic examination versus polymerase chain reaction (PCR)-based methods and DNA sequencing using whole blood and skin lesion samples from patients with suspected leishmaniasis. The presence of Leishmania was determined by microscopy and amplification of 18S ribosomal RNA gene from blood and skin samples of 22 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Therefore, more sensitive methods such as the polymerase chain reaction (PCR) have been developed as an alternative for the diagnosis and identification of Leishmania species. PCR platforms show sensitivity values between 92 and 100% and specificity of 100% ( Reithinger and Dujardin, 2007 ; Shahbazi et al, 2008 ; Mohammadiha et al, 2013 ; Adams et al, 2014 ; Munoz et al, 2016 ). For the amplification of DNA fragments of Leishmania species, the use of genetic targets such as kinetoplast DNA (kDNA), which has a sensitivity of 97% and a specificity of 87%, has been reported in several studies ( Marques et al, 2001 ; Rodriguez et al, 2002 ; Jara et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more sensitive methods such as the polymerase chain reaction (PCR) have been developed as an alternative for the diagnosis and identification of Leishmania species. PCR platforms show sensitivity values between 92 and 100% and specificity of 100% ( Reithinger and Dujardin, 2007 ; Shahbazi et al, 2008 ; Mohammadiha et al, 2013 ; Adams et al, 2014 ; Munoz et al, 2016 ). For the amplification of DNA fragments of Leishmania species, the use of genetic targets such as kinetoplast DNA (kDNA), which has a sensitivity of 97% and a specificity of 87%, has been reported in several studies ( Marques et al, 2001 ; Rodriguez et al, 2002 ; Jara et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples associated with molecular methods have already been widely used for visceral leishmaniasis diagnosis and showed sensitivity equal to or better than bone marrow or splenic aspirates [ 81 , 82 ]. For CL diagnosis, as expected, the blood samples even with leukocyte enrichment showed reduced sensitivity compared to samples obtained directly from the lesion [ 38 , 69 ], but they also showed that the dissemination of the parasite with the detection of DNA in the blood occurs even before the appearance of the mucosal lesion and is persistent after treatment [ 83 , 84 , 85 ]. Previous research has reported the isolation of the parasite in direct culture of blood samples from patients with ML [ 86 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 83%
“…Although in this study, standardized protocol was employed for sample collection and slide preparation, and the same professional examined all the slides, 206 patients would not have been diagnosed if only DP was performed. Molecular tests are more sensitive for TL than for DP, with sensitivity for TL of up to 100% [ 35 , 68 , 69 , 70 ]. As expected, higher sensitivity was observed for molecular tests (PCR) employed in this work, and only 10 samples positive for DP were negative for both molecular tests.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 Molecular tools have been used for the diagnosis of leishmaniasis, owing to their high levels of sensitivity (40-92%) and specificity (57.1-100%). 6,7 However, the requirement for complex equipment and infrastructure means that molecular diagnostic techniques are not suitable for use in remote areas or in the search for active cases (field work). In 2000, Notomi et al 8 designed a new technique known as loop-mediated isothermal amplification (LAMP).…”
Section: Introductionmentioning
confidence: 99%